Analisis Perbedaan Materi Pokok Pembelajaran Akidah pada Kurikulum 2013 dan Kurikulum Prototipe 2022 - Basuki (MA'ALIM: Jurnal Pendidikan Islam, 2024)
The burden of each subject matter of faith in schools in the 2013 curriculum during the COVID-19 pandemic is very heavy because learning for each subject matter is forced to achieve four indicators of competency (spiritual attitudes, social attitudes, knowledge, and skills). This condition is one of the backgrounds for the implementation of the 2022 prototype curriculum starting in the 2022-2023 school year. This study aims to identify and analyze differences in faith’s subject matter in the 2013 curriculum and the 2022 prototype curriculum. This research is library research with the main data sources "2013 curriculum policy" and "2022 prototype curriculum policy". By using content analysis, it has been found that the subject matter of faith in the 2013 curriculum is formulated based on the basic competence based on twelve classes. While the creed material in the 2022 prototype curriculum is formulated based on learning achievement based on six phases. Based on these differences, the subject matter of the 2022 prototype curriculum emphasizes the achievement of essential materials in each phase. Thus, the 2022 prototype curriculum can recover the problem of the burden of each subject matter of faith in schools in the 2013 curriculum during the COVID-19 pandemic.